Interaction of strongly correlated electrons and acoustical phonons: Strong Correlations - Moskalenko, V.A.; Entel, P.; Digor, D.F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We investigate the interaction of correlated electrons with acoustical phonons using the extended Hubbard–Holstein model. The Lang–Firsov canonical transformation allows one to obtain mobile polarons for which a new diagram technique and generalized Wick’s theorem is used. The physics of emission and absorption of the collective phonon-field mode by the polarons is discussed in detail. In the strong-coupling limit of the electron-phonon interaction, and in the normal as well as in the superconducting phase, chronological thermodynamical averages of products of acoustical phonon-cloud operators can be expressed by the products of one-cloud operator averages. While the normal one-cloud propagator has the form of a Lorentzian, the anomalous one is of Gaussian form and considerably smaller. We have established the Mott–Hubbard and superconducting phase transitions in this model.